Improving Goat Meat (Longissimus Muscle) Tenderization by Using Moringa Oleifera Leaves - Hunin AbdElwhab Mohamed Tasnim; Sumarmono Juni; Fatoni Amin; Zeinalabdeen Abdelgadir Frah Amani; Fadhlurrohman Irfan; Muhammad Yusuf Hassan (E3S Web of Conferences)
Moringa oleifera leaves has potential as a natural tenderizing agent for goat meat, explicitly targeting the longissimus muscle. The study aimed to improve goat meat tenderization by using Moringa Oleifera and provide an eco-friendly and health-conscious method for improving the quality of goat meat. Treatments with fresh moringa leaves (as paste 10 gr/100 meat) were applied to goat meat samples (Control = Untreated sample, T1 = treated for 3hr, T2 = treated for 6hr). The treat samples were left in the fridge at temperatures 4 to 3 and 6 hr followed by assessments of texture profile (TPA), pH, color, and cooking loss (CL); the results show texture profile (hardness and toughness) significant (p< 0.05) between control and treat samples, (Adhesiveness et al.) insignificant (p< 0.05), without adverse effects on cooking loss (CL). On the other hand, the Moringa leaves paste increased the PH of treated samples compared with the control. It was some changes in color characteristics, especially in (Redness (a*) and (Yellowness (b*), without adverse effects on (lightness L*); these changes are beneficial for enhancing the visual appeal of particular meat and meat products while also contributing to their nutritional quality to consumers. The present results suggest that Moringa oleifera seems to be a promising source of exogenous enzymes for meat tenderization.